CARACTERÍSTICAS FÍSICAS, QUÍMICAS E MICROBIOLÓGICAS DE QUEIJOS TIPO BRIE E TIPO CAMEMBERT PRODUZIDOS NO BRASIL - Pereira, Antonio Carlos Prestes (2014)
The Brazilian annual production of white mold cheese is around 2,170 tons, the Brie type totals 75% of the production whereas the Camembert type totals 25%; most of the production comes from the states of Minas Gerais and Paraná. Nonetheless, Brazilian legislation does not have a specific Technical Regulation for the Identity and Quality (RTIQ in the Portuguese acronym) for these types of fine cheese, which makes it difficult to have a national standard product “Type”. The aim of this study is to describe the physico-chemical and microbiological properties of these kinds of cheese based on the current official legislation and on an analytical methodology. In addition, the study proposes a specific RTIQ (Technical Regulation for Identity and Quality) for humidity, fat, protein, defatted dry extract, ash, calcium and sodium. The study used a descriptive and experimental methodological approach, which included the collection of Brie and Camembert cheese samples from the summer and winter productions, and a French sample of the same types of cheese to learn about the composition of through the year. The average weight of Brie cheese was 119.87 g, with an average height of 30.31 mm and an average diameter of 131,28 mm. The average whiteness index (WI) of the surface was 70.63 and 89.37 for the center. The texture profile in average values was as follows: -590.12 g for adhesion, 0.88 g, 0.73 for hardness, 0.73 for cohesiveness, 151,86 for chewiness and 0.26 for resilience. The physico-chemical composition of Brie heese in a 95% reliable interval was the following: moisture between 41.80 and 53.10 g.100g-1, fat between 49,65 and 62,59 g.100g-1, defatted dry extract 19.43 and 23.23 g.100g-1, protein between 14.20 and 20.00 g.100g-1, carbohydrate between 1.80 and 7.60 g.100g-1, ashes between 2.80 and 3.40 g.100g-1, the amount of sodium ranged between 112.80 and 661.20 mg.100g-1 and an amount of calcium between 323.90 and 848.10 g.100g-1. The average weight of Camembert cheese was 195.74 g, with an average height of 33.44 mm and an average diameter of 88.05 mm. The average whiteness index (WI) for the surface was 91.82 and 72.29 for the center. The texture profile in average values was as follows: -380.15 g for adhesion, 0.60 g for hardness, 0.50 for cohesiveness, 158,87 for chewiness and 0.19 for resilience. The physico-chemical composition of Camembert cheese presented in a 95% reliable interval moisture between 31.10 and 57.50 g.100g-1, fat between 52,43 and 63,3 g.100g-1, defatted dry extract from 20.13 to 23.20 g.100g-1, protein from 14.27 to 19.73 g.100g-1, carbohydrate from 0.80 to 5.44 g.100g-1, ashes from 3.09 to 4.05 g.100g-1, the amount of sodium ranged between 72.50 and 577.50 mg.100g-1 and, an amount of calcium between 282.80 and 788.80 mg.100g-1. L. monocytogenes was found in a sample of Camembert cheese. The other samples of both types of cheese presented a microbiological profile within the parameters set by the national legislation.